Rapid automatized naming in relation to some other reading components and reading skills of second graders - Abolafya, Pelin Bella. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2008., 2008)
The aim of the study was to investigate the role of Rapid Automatized Naming (RAN) in the components of reading process (word reading, reading comprehension, oral reading fluency, letter knowledge) among second grade students with varying reading abilities (poor and good readers). The participants were 118 second grade students. To see the relationships among RAN and some other components of reading, correlational analysis were conducted. To examine the differences in terms of reading levels in RAN and other components of reading, t test analysis and one-way multivariate analysis of variance (MANOVA) were conducted. Correlational analyses indicated that RAN numbers were significantly correlated with RAN letters, sight-word reading, non-word reading, and oral reading fluency in poor readers. Furthermore, the results showed that RAN letters were significantly correlated with sight-word reading, non-word reading, oral reading fluency, reading comprehension, and letter knowledge in poor readers. Neverthless, except sight-word reading, there were no significant correlations between RAN numbers and other measures in good readers. Furthermore, except non-word reading, there were no significant relationships between RAN letters and other measures in good readers. One-way multivariate analysis of variance (MANOVA) and t-test results indicated that, based on the reading level (poor and good readers), there were significant differences in RAN numbers, RAN letters, sight-word reading, non-word reading, reading comprehension and letter knowledge. Findings of the study indicated that RAN tasks were shown to be related to the some other components of reading for poor readers. Results also revealed that poor readers have a general deficit in rapid naming tasks as well as other reading related tasks. However, further research is needed to examine the predictive role of RAN with different reading abilities.
Keywords: Reading (Elementary)